Obesity Is Associated With Increased Susceptibility to Influenza A (H1N1pdm) but Not H3N2 Infection. (9th July 2020) - Maier, Hannah E; Kuan, Guillermina; Gresh, Lionel; Lopez, Roger; Sanchez, Nery; Schiller, Amy; Ojeda, Sergio; Harris, Eva; Balmaseda, Angel; Gordon, Aubree
Abstract: Background: Obesity has been shown to increase the risk of severe outcomes and death for influenza virus infections. However, we do not understand the influence of obesity on susceptibility to infection or on nonsevere influenza outcomes. Methods: We performed a case-ascertained, community-based study of influenza transmission within households in Nicaragua. To investigate whether obesity increases the likelihood of influenza infection and symptomatic infection we used logistic regression models. Results: Between 2015 and 2018, a total of 335 index cases with influenza A and 1506 of their household contacts were enrolled. Obesity was associated with increased susceptibility to symptomatic H1N1pdm infection among adults (odds ratio [OR], 2.10; 95% confidence interval [CI], 1.08–4.06) but not children, and this association increased with age. Among adults with H1N1pdm infection, obesity was associated with increased likelihood of symptoms (OR, 3.91; 95% CI, 1.55–9.87). For middle-aged and older adults with obesity there was also a slight increase in susceptibility to any H1N1pdm infection (OR, 1.20; 95% CI, .62–2.34). Body mass index (BMI) was also linearly associated with increased susceptibility to symptomatic H1N1pdm infection, primarily among middle-aged and older women (5-unit BMI increase OR, 1.40; 95% CI, 1.00–1.97). Obesity was not associated with increased H3N2 susceptibility or associated symptoms. Conclusions: We found that, among adults, obesity is associated with susceptibility to H1N1pdm infection and with symptoms associated with H1N1pdm infection, but not with susceptibility to H3N2 infection or associated symptoms. These findings will help target prevention efforts and therapeutics to this high-risk population. Abstract : We found that, in adults, obesity is associated with increased susceptibility to H1N1pdm infection and this association increases with age. Obesity was not associated with H3N2 susceptibility.